Replacing hexane with 2-methyloxolane for defatting soybean meal fed to dairy cows: Effects on dairy performance and nitrogen partitioning - V. Menoury; A. Ferlay; C. Ginane; G. Cantalapiedra-Hijar; S. Lemosquet; D. Andueza; G.G.R. Leday; J. Engel; P. Nozière (Journal of Dairy Science)
ABSTRACT: 2-Methyloxolane (MeOx) is a promising candidate for replacing hexane as a solvent for defatting soybean meal (SBM). However, the use of MeOx requires adjustments of the oil extraction process that may affect the nutritive value of SBM. This study aims to ensure that process modifications due to the use of MeOx do not affect the protein value of SBM for dairy cows. Sixteen primiparous Holstein dairy cows were included in a 4 × 4 Latin square design experiment. The 4 dietary treatments consisted of hexane-defatted SBM, MeOx-defatted SBM, or a combination in various proportions: 100% hexane-defatted SBM (control diet, HEX), 67% hexane-defatted SBM plus 33% MeOx-defatted SBM (33MeOx), 33% hexane-defatted SBM plus 67% MeOx-defatted SBM (67MeOx), and 100% MeOx-defatted SBM (100MeOx). The diets contained 16% SBM and were iso-CP. Feed, rumen fluid, blood, urine, feces, and milk samples were collected. The traits measured were indicators of ruminal protein degradation (NH3 concentration and branched-chain volatile fatty acid proportion in the rumen fluid), N metabolism (plasma concentrations of essential AA, 1-methylhistidine, and 3-methylhistidine), N partitioning and N use efficiency (N use efficiency for milk production, N isotopic discrimination between plasma and diet), and milk quality (protein and fat contents, N fractions, hexane and MeOx residues). Statistical analyses used difference and equivalence tests. Replacing hexane-defatted SBM with MeOx-defatted SBM resulted in likely equivalent dairy performance, N partitioning, and N use efficiency for milk production, although some indicators suggested slight rumen and digestive alterations that may have subtly affected whole-body N metabolism. A subset of 6 cows was selected for analysis of solvent residues in milk. Even though hexane-defatted SBM contained only 11 mg/kg DM of n-hexane residues, 5 out of 6 milk samples from cows fed HEX presented detectable n-hexane residues, whereas only 1 out of 6 milk samples from cows fed 100MeOx presented detectable n-hexane residues. Therefore, n-hexane residues in milk tended to be detected more often when cows were fed hexane-defatted SBM compared with MeOx-defatted SBM. The MeOx-defatted SBM contained 977 mg/kg DM of MeOx residues, but only 2 out of 6 milk samples from cows fed 100MeOx and 0 out of 6 milk samples from cows fed HEX presented detectable MeOx residues. These results raise prospects for using MeOx as a hexane substitute for defatting SBM fed to dairy cows, although further studies are needed to confirm the slight differences observed here in N metabolism.